2017
DOI: 10.1038/labinvest.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of sun-protected sites: a review of clinical, histological, and molecular features

Abstract: In most cases of cutaneous melanoma, ultraviolet (UV) radiation is recognized as a prominent risk factor. Less is known regarding the mechanisms of mutagenesis for melanoma arising in sun-protected sites, such as acral and mucosal melanoma. Acral and mucosal melanoma share many common features, including a late age of onset, a broad radial growth phase with prominent lentiginous growth, the presence of field cancerization cells, and, in most cases, lack of a precursor nevus. In addition to early chromosomal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 60 publications
0
59
0
5
Order By: Relevance
“…Up to date, promising recurrent regions of gains and losses were identified (5) and confirmed by several investigations (4,7,8), in particular amplified portions of HSA 12q and 5p, which encode for genes as CDK4 and TERT, respectively (7). In addition, CCND1, KIT, and VEGFRA were proposed by a recent review (10) as targets for future investigations. hMMs represent only the 1.3% of all reported melanomas (1) and they may arise from different sites, as head-and-neck, female genital tract, and anal/rectal mucosa, with a respective 5 years survival rate of 31.7, 11.4, and 19.8%, while cMM has a 5 years survival rate of 80.8% (1).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Up to date, promising recurrent regions of gains and losses were identified (5) and confirmed by several investigations (4,7,8), in particular amplified portions of HSA 12q and 5p, which encode for genes as CDK4 and TERT, respectively (7). In addition, CCND1, KIT, and VEGFRA were proposed by a recent review (10) as targets for future investigations. hMMs represent only the 1.3% of all reported melanomas (1) and they may arise from different sites, as head-and-neck, female genital tract, and anal/rectal mucosa, with a respective 5 years survival rate of 31.7, 11.4, and 19.8%, while cMM has a 5 years survival rate of 80.8% (1).…”
Section: Introductionmentioning
confidence: 67%
“…Among the genes related to cell proliferation and mitosis, GRHL2, a transcription factor able to bind the promoter region of TERT, was found to be gained. Although TERT is one of the most frequently involved genes in human non UV-induced melanomas (7,10) it has never been found amplified in COMs. However, the gain of GRHL2 suggests that TERT expression may play a role in COMs.…”
Section: Discussionmentioning
confidence: 99%
“…Since COM shares some features with its human counterpart such as histologic phenotype, tumour genetics and clinical behavior, it is increasingly under evaluation as a spontaneous animal model of human non‐UV induced/sun‐protected sites melanomas, especially acral and mucosal melanomas . Some of the mechanisms of mutagenesis for human melanoma arising in sun‐protected sites were recently evaluated, and early chromosomal instability in CCND1, KIT, PDGFRA and TERT was the most common genetic alteration reported . In particular, chromosomal instability surrounding Cyclin D1 is the most frequently described in human acral and mucosal melanomas where copy number gains and amplification are detected in 31 to 45% of cases .…”
Section: Introductionmentioning
confidence: 99%
“…Melanomas arising on acral surfaces (defined as the glabrous skin of the palms and soles as well as the nail apparatus) are relatively rare (~1.5%‐3% of melanoma cases) yet confer comparatively lower survival rates vs other types of cutaneous malignant melanomas (CMMs). Interestingly, most acral melanomas arise on relatively sun‐protected skin, with some studies suggesting that the heel of the foot is the most common site . As such, genetic damage from ultraviolet radiation (UVR) is thought to be less of a contributor to acral melanoma formation .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most acral melanomas arise on relatively sun‐protected skin, with some studies suggesting that the heel of the foot is the most common site . As such, genetic damage from ultraviolet radiation (UVR) is thought to be less of a contributor to acral melanoma formation . Indeed, genetic studies have shown that acral melanomas carry significantly less of a UVR mutation burden and possess acral‐melanoma‐specific driver mutations, which together suggest an alternative pathogenesis of acral melanoma vs other types of CMM.…”
Section: Introductionmentioning
confidence: 99%